Application of dental pulp stem cell-conditioned medium combined with deep cryopreservation of autologous cranial flaps - Ye Liu; Yonghao Liu; Zhifei Ye; Xinxin Wang; Junyi Li; Peter L. Mei; Li Duan; Ben Wang; Chun Xu; Wei Xiong; Yan He; Qingsong Ye (Stem Cell Research & Therapy)
Abstract Background Autologous cranial flaps preservation after decompressive craniectomy (DC) is crucial for cranioplasty, yet standard cryopreservation carries high complication rates 15–35%, primarily infections and bone resorption. These complications frequently necessitate surgical revisions and increase morbidity risks. Current methods lack standardized preservation solutions that simultaneously ensure osteocyte survival and prevent microbial growth. Developing integrated bacteriostatic and osteoprotective storage media remains an urgent unmet need to enhance patient outcomes. Objectives This study investigates optimized preservation protocols for autologous cranial flaps to mitigate post-cranioplasty complications, while evaluating the preservative efficacy and clinical translation potential of dental pulp stem cell-conditioned medium (DPSC-CM) as a novel osteogenic storage solution. Methods Dental pulp stem cells (DPSCs) were cultured in serum-free medium to generate DPSC-CM. To evaluate the preservation efficacy of DPSC-CM, first, DPSC-CM was preliminarily evaluated by examining the cell viability after freezing and resuscitation. Second, a murine critical-size calvarial defect model was surgically established. Autologous cranial flaps underwent 4-week storage in experimental preservation solutions (DPSC-CM versus conventional cryoprotectants) were reimplanted. Postoperative bone regeneration was systematically quantified through high-resolution micro-CT analysis and histomorphometric evaluation of bone regeneration capacity. Given DPSC-CM’s osteopreservative potential, in vitro analyses confirmed DPSC-CM’s osteogenic/angiogenic capacity through proliferation/migration assays, osteogenic differentiation, and biomarker quantification. Results DPSC-CM demonstrated superior efficacy in cell preservation. Studies in a mouse model of cranial defects showed that the cranial flaps preserved with DPSC-CM in combination with deep cryopreservation (-196 °C) showed significantly better bone healing after cranioplasty than the other groups, and their neoangiogenic and anti-inflammatory abilities were also significantly better than those of the other groups. DPSC-CM was found to be superior to DPSCs in the osteogenesis of mouse embryonic osteoblast cells (MC3T3-E1 cells) and the angiogenesis of human umbilical vein endothelial cells (HUVECs). Conclusions Considering the superiority of osteogenesis and vascularization in vivo and in vitro, as well as the modulating of the local inflammatory microenvironment, DPSC-CM synergistic combination deep cryopreservation emerges as a novel strategy of preserving cranial flaps after DC. This multidisciplinary approach establishes a transformative framework for advancing autologous cranial flaps storage technologies, demonstrating translational promise through biological optimization of traditional cryopreservation protocols.